Core issues, case studies, and the need for expanded Legacy African American genomics - Jackson, Fatimah; Clinton, Carter; Caldwell, Jennifer (Frontiers in Genetics, 2023)
African American genomic studies have a tangled and convoluted history in western science. Overall, the quality and quantity of existing studies underrepresent African American genomic diversity. In every category of genomic testing (i.e., diagnostic, clinical predictive, pharmacogenomic, direct-to-consumer, and tumor testing), African Americans are disproportionately underrepresented compared to European Americans. Yet African Americans have historically borne the brunt of the earliest biomedical studies using to generate primitive concepts of genetics. As exploited victims of these investigations, African American men, women, and children were subjected to ethics-free western science. Now that safeguards have been added, underrepresented and marginalized people, once the convenient targets of western science, are now excluded from its health-related benefits. In this paper the core issues affecting African American genomic studies are addressed and two case studies presented to highlight the current status of genomic research in this population. The first case study is from the New York African Burial Ground Project where genomic studies of grave soil derived DNA has yielded insights into the causes of death of 17th and 18th Century African Americans. The second case study is from research among the Gullah Geechee peoples of the Carolina Lowcountry. Here, the connection between genomic studies and health disparities is highlighted. The paper provides recommendations for enhancing the inclusion of African Americans in global genomic databases, identifies the rationale for such inclusion, and enumerates the benefits of such inclusion.